Verso la neutralità climatica di architetture e città green Approcci, indirizzi, strategie, azioni - Tucci, Fabrizio (Architettura, design, territorio, 2023)
The geo-political and climatic-environmental context in which we are living increasingly affects the way we live and inhabit, in the awareness that global emissions of pollutants have reached the threshold of 421 ppm of carbon - 50 percent more than in the pre-industrial era - and that the scarcity of material and immaterial resources is advancing inexorably. This calls for an immediate change of pace in the design approach, with particular attention to the increasingly scarce environmental resources used to meet the demand for energy end-uses. Approaches, strategies and design actions to regenerate urban districts and existing architectures to achieve full climate neutrality - through technological environmental solutions articulated on the six strategic axes of energy transition, bioclimatic effectiveness, resource circularity, functional mix, sustainable mobility, and green and gray CO2 subtraction - become solid milestones to propose new models of responsible and sustainable development, capable of improving the quality of the environment through integrated, interscalar and multidisciplinary approaches.The objective of this book, the result of years of intense research activity still under development, is the construction of a key methodological framework as a reference for the definition of strategic lines and innovative technological solutions that, in pursuit of the objectives of climate neutrality, are at the same time aimed at improving environmental, microclimatic, ecological and energy performance, increasing the usability and livability of public spaces and raising the environmental quality and bioclimatic well-being. The applicative effects of the research are measured by the dimension of design experimentation aimed at the environmental redevelopment and regeneration of architectures, neighborhoods and urban districts, testing the improvements achieved in terms of decreasing carbon emissions, so as to allow a critical evaluation of the obtained results.